Emulsifying Properties of Dietary Fiber from Different Sources - Yao WANG; Xue ZHAO; Hao WU; Xinglian XU (Shipin gongye ke-ji)
Five kinds of dietary fibers (rice bran, banana peel, apple peel, oat bran and citrus peel) from different sources were selected as row materials to prepare dietary fiber-based O/W emulsions and the ability of various types of dietary fibers to stabilize emulsions at different concentrations (1%, 2%, 3%) were investigated by analyzing Zeta potential, particle sizes, creaming index, Turbiscan stability index and rheological properties. The results showed that when the fiber concentration increased from 1% to 3%, the particle size D4,3 of all emulsions decreased significantly (P<0.05) by 49.94%, 44.02%, 33.68%, 1.01% and 0.17%, respectively, for rice bran, banana peel, apple peel, oat bran and citrus dietary fiber emulsions. The absolute value of Zeta potential and apparent viscosity increased with increasing fiber concentration, and both reached the maximum value in the rice bran dietary fiber emulsion with fiber concentration of 3% (Zeta potential value: −59.45 mV; viscosity: 15.88 mPa·s). The results of storage stability suggested that with the extension of storage time, oat bran dietary fiber emulsion and citrus fiber emulsion showed obvious oil-water layered, and the emulsification ability was lower than that of other groups. There was obvious clear layer shown at the bottom of rice bran, banana peel and apple peel dietary fiber emulsion, and the creaming index decreased gradually with the increase of fiber concentration. When the concentration reached 3%, the rice bran dietary fiber emulsion after 5 d of storage showed the lowest (27.43%) creaming index and the highest stability. In conclusion, rice bran dietary fiber exhibited the best emulsifying property among the five dietary fiber emulsions, and the higher the concentration, the higher the stability of the emulsion. This study demonstrates the excellent potential of by-product dietary fiber as an emulsifier to stabilize pre-emulsion, which is expected to be used as a fat substitute in food system.